Coronary arteriographic study of mild angina. Issue 7 (July 1975) - Walsh, W; Rickards, A F; Balcon, R
Abstract : The results of coronary arteriography, exercise, and pacing stress testing in 50 young patients with mild angina are analysed. There was a significant correlation between the results of stress tests and the secerity of disease. There were, however, patients with severe disease and negative tests. Fifty-six per cent of patients had disease which potentially could have been surgically treated. It is concluded that coronary arteriography is indicated in these patients with mild symptoms.